ISSUES OF RESPONSIBILITY FOR CRIMES DANGEROUS TO LIFE OR HEALTH - Khaydarov Shukhratjon Jumaevich (International Journal of Business, Law and Political Science, 2024)
General Background: Crimes that endanger life or health are critical areas of study within legal scholarship, reflecting societal concerns about public safety and individual well-being. Specific Background: This article examines the nuances of responsibility associated with such crimes, reviewing various definitions proposed by legal scholars and presenting a novel definition of life- or health-threatening crimes. Knowledge Gap: Despite existing literature, there remains a lack of comprehensive frameworks that systematically categorize these crimes, particularly regarding their objective and subjective dimensions. Aims: The aim of this study is to elucidate the components of crimes that threaten life or health, exploring their classifications based on object, subject, and methods of commission. Results: The findings reveal a structured analysis of the objective and subjective elements of these crimes, alongside a detailed classification system that enhances understanding of their diverse manifestations and the associated legal responsibilities. Novelty: This article contributes to the field by offering an original definition of life- or health-threatening crimes and a classification framework that integrates both traditional and contemporary perspectives. Implications: The conclusions drawn underscore the necessity for legal systems to adopt clearer definitions and classifications, which could improve the enforcement of laws and enhance protective measures for individuals at risk. Future research should focus on empirical studies to further refine these classifications and examine their practical implications within various legal contexts.